The Integration of Islamic Education Value in Strengthening Higher Education Students’ Peace-loving Character - Eli Karliani; Ahmad Saefulloh; Triyani Triyani (Institut Agama Islam Negeri Kendari, 2021)
Very important to provide understanding and awareness to students to manage religious differences into peace-loving characters. In Islamic education, it can be implemented in several ways, such as opposing violent methods and emphasizing the means of deliberation, upholding the values of togetherness, accepting the existence of various human attributes. The method of this study comprised of FGD in examining the curriculum of Islamic Education in Higher Education; developing Islamic Education curriculum models in strengthening the peace-loving character (the learning tools include syllabus, lesson plans, Media, and Evaluation). The results of the study demonstrated that the Islamic education curriculum in tertiary institutions was not yet oriented to human beings peace-loving character, and limited understanding was identified among the students regarding the implementation of that character in the classroom settings. The religious education provided at Palangka Raya University has not yet implemented interfaith education. It required the media to apply the students’ understanding regarding the nature of human differences in activities involving different religions on a project. The Islamic Education Learning Toolkit was based on a student-based problem project with interfaith discussion techniques, making students solve problems that occur in the environment involving all students of different religions who take religious courses in odd semester of 2019/2020.